2020
DOI: 10.1017/s136898002000525x
|View full text |Cite
|
Sign up to set email alerts
|

High sugar content and body mass index: modelling pathways around the first 1000 d of life, BRISA cohort

Abstract: Objective: Few studies are focused on sugar consumption around the first 1000 d of life. Thus, this work modelled the pathways linking the consumption of sugary drinks in pregnancy and maternal pre-gestational BMI to early child’s exposure to products with high sugar content and to BMI z-score in the second year of life. Design: BRISA cohort, São Luís, Brazil was used from the baseline to the follow-up at the second year of life. Setting: A theoretical model was constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The frequency of added sugar consumption by the mother may be associated with maternal obesity [32]. Maternal obesity may explain the early and high sugar exposure [18] and obesity [18] in offspring. These pathways could explain the association of maternal obesity with childhood caries [19].…”
Section: Proposed Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of added sugar consumption by the mother may be associated with maternal obesity [32]. Maternal obesity may explain the early and high sugar exposure [18] and obesity [18] in offspring. These pathways could explain the association of maternal obesity with childhood caries [19].…”
Section: Proposed Theoretical Modelmentioning
confidence: 99%
“…The sugar exposure and obesity (higher BMI/Age z-score) in children may increase with age [33]. In addition, the consumption frequency of added sugars may be associated with obesity in childhood [18] and with the chronic oral disease burden in early childhood [14,18,34], while the last two variables may be correlated with each other.…”
Section: Proposed Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation for the association between SSB exposure and allergies especially involves three main mechanisms: Modulate Children's Mechanism, AGE's Mechanism, and Dysbiosis' Mechanism (Figure 2). A higher consumption of SSBs during pregnancy resulted in a higher percentage of calories from sugary products in children at two years of age [7]. These findings involve genetic and environmental alterations, which can lead to a preference for sweets due to changes in taste, as well as the ingestion of greater amounts of sugars in offspring [27].…”
Section: Discussionmentioning
confidence: 97%
“…[16][17][18] Moreover, a recent cohort study showed that maternal obesity and high consumption of sugary drinks during pregnancy increased the risk of early exposure (before the second year of life) and high exposure of the child to added sugars, showing perpetuation of unhealthy dietary habits in the first 1000 days of life. 49 Therefore, maintaining oral health, strengthening and improving oral health knowledge during pregnancy is a critical and promising step in the prevention of ECC and other maternal and child oral health indicators throughout life. The formation of primary teeth and some early erupting permanent teeth (permanent first molars and incisors) begin during pregnancy.…”
Section: The Pregnancy Periodmentioning
confidence: 99%